COVID-19: En este momento podría ser útil el tratamiento antiviral en casos leves - Ticona Chávez, Eduardo (2020)
COVID-19's lethality as well as its rapid spread are responsible for the current world crisis; therefore, from the beginning, drugs with antiviral action against this agent were sought. It is impossible, for now, to know which person in a mild state will develop a high viral load or have a predisposition to develop an extreme response from the immune system, but early treatment in mild cases would not only guarantee greater efficacy, but would avoid severe cases. Currently, there are no double blind, randomized clinical trials or meta-analyzes available to make safe decisions; meanwhile, the pandemic is advancing in our country, generating pain and death. In this context, in Peru, scientific societies have expressed the need for the use of antiviral drugs, even with little evidence, based on the probability of success prior to treatment, for their in vitro effects and for their early clinical effects, such as: chloroquine, hydroxychloroquine, azithromycin, lopinavir, ritonavir. Thus, in the country since march 29, 2020, there is a technical standard from the Ministry of Health, which facilitates the use of these at the national level for moderate and severe cases. We believe that under a structured system, first-level care centers could treat mild cases of COVID-19. Our country, through strategies for the prevention and control of TB and ITS/HIV/AIDS, has experience in managing treatment programs at this level. The costs will be less than those required to strengthen the third level of care.